Say cheese and die! - Stine, R. L.; Payne, Matthew D. (New York : Scholastic, 2009)
Greg is excited when he finds a mysterious old camera, but excitement turns to fear when the pictures he takes foretell terrifying events.
"Now with bonus features!"--Cover.
5.4
5-8
Keywords: Cameras -- Juvenile fiction; Photography -- Juvenile fiction; Prophecy -- Juvenile fiction; Cameras -- Fiction; Horror stories; Photography -- Fiction; Prophecy -- Fiction; Cameras -- Fiction; Horror fiction; Photography -- Fiction; Prophecies -- Fiction; Horror fiction